KAJIAN KEBIJAKAN HUTAN KOTA: STUDI KASUS DI PROVINSI DAERAH KHUSUS IBUKOTA JAKARTA (DKI) - Subarudi Subarudi; Ismayadi Samsoedin (Jurnal Analisis Kebijakan Kehutanan, 2012)
Special Capital Territory (DKI) of Jakarta is known as one of the flood-prone area along with the rise of sea level due to global warming. This condition is worsening with the significant reduction of open green area or known as Ruang Terbuka Hijau (RTH) from 35% in 1965 to 9,3% in 2009. This study on policy development of urban forest in DKI Jakarta is really needed as a learning process for urban developers in Indonesia. This study aims to evaluate the implementation of urban forest policy which has been managed and operated by provincial government (Pemda) of DKI Jakarta. The results showed that development on urban forest is undoubtedly able to decrease the level of vulnerability from flood and at the same time beautify and sustain the green environment. After the release of PP no. 63 in 2002 about Urban Forest and UU No. 26 in 2007about National Land Use, the provincial government of DKI Jakarta has not developed any local regulations related to the regulations above. However, a lot of efforts have been done in the ground to support the development of urban forest through the increase of RTH. The government of DKI Jakarta is still trying to increase the area of RTH consistently by demolishing 93 buildings in the river side of Kalibaru and closing 27 gasoline pump stations for public (SPBU) which are located in the green area and stipulating their function as RTH. Funding can be collected by the Government of DKI Jakarta from various sources such as APBD, APBN, Public Tax and CSR incentives from national and multinational large companies which located in Jakarta, as well as international donors who pay attention to environment conservation.